2015
DOI: 10.1055/s-0035-1564721
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Chin-tuck Maneuver to Facilitate Swallowing in Neurologic Dysphagia

Abstract: Introduction The chin-tuck maneuver is the most frequently employed postural maneuver in the treatment of neurogenic oropharyngeal dysphagia caused by encephalic vascular strokes and degenerative diseases. Objective The purpose of this study was to investigate the effectiveness of this maneuver in patients with neurogenic dysphagia and factors that could interfere in it. Methods In this retrospective cohort, we analyzed the medical files and videofluoroscopy exams of 35 patients (19 male – 54% and 16 female – … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 16 publications
0
38
0
2
Order By: Relevance
“…This study made a similar attempt but included deglutition episodes, and found prolonged swallow-induced respiratory apnoea with chin-down position with the differences reaching statistical significance in higher bolus volumes. Increased duration of swallow apnoea may be a functional consequence of altered anatomical dimensions of pharyngeal structures with chindown [23,39] and may be one of the factors that effectively augment airway decoupling in persons with dysphagia [40,41]. However, this finding implies that this posture may not be effective in persons with respiratory insufficiency, and associated swallowing difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…This study made a similar attempt but included deglutition episodes, and found prolonged swallow-induced respiratory apnoea with chin-down position with the differences reaching statistical significance in higher bolus volumes. Increased duration of swallow apnoea may be a functional consequence of altered anatomical dimensions of pharyngeal structures with chindown [23,39] and may be one of the factors that effectively augment airway decoupling in persons with dysphagia [40,41]. However, this finding implies that this posture may not be effective in persons with respiratory insufficiency, and associated swallowing difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…Muscle activity and tongue kinematics differ during head-down drinking compared with suckling in infant pigs [1], and food consistency has been found to alter motor patterns and kinematics during feeding [9,10]. Similarly, head posture affects the coordination of swallowing and breathing: the 'chin tuck' is a common practice to alter swallowing kinematics and reduce aspiration in adult humans [11][12][13]. Changes in food texture and food acquisition occur across the weaning process and influence muscle function and kinematics.…”
Section: Introductionmentioning
confidence: 99%
“…In the treatment of patients with dysphagia, compensatory techniques and rehabilitation strategies to improve dysphagic swallows by altering bolus flow have been widely designed and used (Ohmae et al, ; Solazzo et al, ). Postural adjustments are one such compensatory technique, improving dysphagic swallows by changing the angle and position of the head and body, thereby resulting in changing the velocity and direction of bolus flow (Ertekin et al, ; Park, Seo, Ko, & Park, ; Saconato, Chiari, Lederman, & Gonçalves, ; Shanahan, Logemann, Rademaker, Pauloski, & Kahrilas, ). Both the reclining (Park et al, ) and the chin‐tuck position (Saconato et al, ) reduce aspiration in dysphagic patients.…”
Section: Introductionmentioning
confidence: 99%
“…Postural adjustments are one such compensatory technique, improving dysphagic swallows by changing the angle and position of the head and body, thereby resulting in changing the velocity and direction of bolus flow (Ertekin et al, ; Park, Seo, Ko, & Park, ; Saconato, Chiari, Lederman, & Gonçalves, ; Shanahan, Logemann, Rademaker, Pauloski, & Kahrilas, ). Both the reclining (Park et al, ) and the chin‐tuck position (Saconato et al, ) reduce aspiration in dysphagic patients. The clinical benefits of applying postural adjustments singly or in combination are effective in 80–90% of dysphagia patients(Logemann, Rademaker, Pauloski, & Kahrilas, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation